2015
DOI: 10.1515/ap-2015-0073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body size on the abundance of ectoparasitic mites on the wild rodent Oligoryzomys nigripes

Abstract: The abundance of parasites on a host can be affected by several factors; in this study, we investigated the influence of sex and body size of the host rodent Oligoryzomys nigripes on the abundance of ectoparasitic mites (Acari: Mesostigmata). The generalized linear model indicated that body size (indicative of age) of the host rodent O. nigripes significantly contributed to the variation in the abundance of mites on host rodents at the Experimental Station of Itirapina. This trend of increased parasitism on ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
1
6
0
4
Order By: Relevance
“…Additionally, we do not find an association between the abundance and prevalence of G. wolffsohni and the sex and weight of their host. This agrees with other authors who found that Gigantolaelaps peruviana (Ewing) abundance was not related to the sex and weight of its host; however, they found an association in other Laelapidae mites (Fernandes et al 2012(Fernandes et al , 2015.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, we do not find an association between the abundance and prevalence of G. wolffsohni and the sex and weight of their host. This agrees with other authors who found that Gigantolaelaps peruviana (Ewing) abundance was not related to the sex and weight of its host; however, they found an association in other Laelapidae mites (Fernandes et al 2012(Fernandes et al , 2015.…”
Section: Discussionsupporting
confidence: 92%
“…Even though we did not find association between the abundance and prevalence of G. wolffsohni with the ecoregions, previous studies have determined that these factors can affect its, since different host's densities in different areas influence the frequency of intraspecific contacts (Fernandes et al 2012(Fernandes et al , 2015. In this aspect, O. longicaudatus has been reported as a rodent with high vagility (Palma et al 2007), which means a higher level of dispersion for their parasites (Poulin 2007).…”
Section: Discussionmentioning
confidence: 54%
“…With more activity and mobility, they have a better chance for increased exposure to ectoparasites and chigger foci in the environment than juvenile animals (Webber et al ., 2015; Matthee et al ., 2020). Another consideration is that animals with a larger body mass or BMI provide a larger surface area for different ectoparasite species to feed on (Fernandes et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the contact networks seems to have had a greater influence on the mite burden in the interaction between G. oudemansi and O. paricola than the rodent characteristics, such as body size, sex and age, although many studies have demonstrated a relationship between these host characteristics and abundance of ectoparasites (Fernandes et al ., 2012, 2015; Hammond et al ., 2019) and endoparasites (Abu-Madi et al ., 2005; Seltmann et al ., 2019; Bellay et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity in parasite exposure and susceptibility to infection between hosts generate different levels of parasite aggregation among host samples (Poulin, 2013; Gourbière et al ., 2015). Many of the published studies on the interaction of ectoparasite and mammalian hosts have investigated the parasitic burden related to host and parasite traits or environmental characteristics (Perez-Orella and Schulte-Hostedde, 2005; Christe et al ., 2007; Brunner and Ostfeld, 2008; Presley and Willig, 2008; Várfalvyová et al ., 2011; Viljoen et al ., 2011; Fernandes et al ., 2012, 2015; Colombo et al ., 2015; Hammond et al ., 2019; Kiene et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%